ANALISIS SIMBOLIK STRUKTURAL BURUNG ENGGANG PADA MASYARAKAT DAYAK - Hidayat, Manarul (Universitas Lancang Kuning, 2021)
Hornbills or Buceros sp. are often used in various Dayak society activities, both of body parts and body illustrations. It shows that hornbills means very important for Dayak society. The importance and sacredness of hornbills can be seen through the structural symbolic concept of Levi-Strauss, which sees myth as starting from its structure before developing into a set of objects and phenomena in the application. Hornbills are believed to play an important role in various aspects of life, through this found concept development that includes objects and phenomena such as buildings, clothing, weapons, leadership and brotherhood, performances, and ceremonies.